2005
DOI: 10.1007/s10804-005-1324-z
|View full text |Cite
|
Sign up to set email alerts
|

Husbands' and Wives' Attachment Orientations and Depressive Symptoms: Predictors of Positive and Negative Conflict Behaviors in the Marriage

Abstract: The present study examined both husbands' and wives' attachment orientations and depressive symptoms in predicting reports of marital conflict behaviors. Married couples (N = 60) completed questionnaires to assess their attachment orientations, depressive symptoms, and perceptions of positive and negative conflict behaviors in the marital relationship. Using hierarchical regression analyses, statistical models were tested wherein husbands' and wives' reports of marital conflict behaviors were regressed on thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Our findings supported partial mediation for couples’ conflict styles, suggesting that additional factors may play important roles such as couples’ attachment (Marchand-Reilly & Reese-Weber, 2005), attributions (Heene et al, 2007), personality characteristics (Uebelacker & Whisman, 2006), or biological/genetic substrates which may predispose individuals to have greater risk for developing depression in response to conflict (Rice, Harold, Shelton, & Thapar, 2006). Our study examined depressive symptoms in a community sample; different relations might be found for clinical samples of depressed individuals or for couples seeking couples’ therapy.…”
Section: Discussionsupporting
confidence: 68%
“…Our findings supported partial mediation for couples’ conflict styles, suggesting that additional factors may play important roles such as couples’ attachment (Marchand-Reilly & Reese-Weber, 2005), attributions (Heene et al, 2007), personality characteristics (Uebelacker & Whisman, 2006), or biological/genetic substrates which may predispose individuals to have greater risk for developing depression in response to conflict (Rice, Harold, Shelton, & Thapar, 2006). Our study examined depressive symptoms in a community sample; different relations might be found for clinical samples of depressed individuals or for couples seeking couples’ therapy.…”
Section: Discussionsupporting
confidence: 68%
“…Considering this finding, we predicted that depression would have a positive actor effect on ERS. We also predicted that depression would have a negative actor and partner effect on RMB because depression was associated with the actor and partner's catastrophic communication, such as withdrawal or negative attitudes (Marchand-Reilly & Reese-Weber, 2005). In addition, we hypothesized that depression would have a negative actor effect and a negative partner effect on relationship satisfaction, because depression interferes with the relationship satisfaction of oneself and a partner (Katz, Beach, & Joiner, 1999).…”
Section: Effects Of Depression and Ers On Rmb And Relational Satisfacmentioning
confidence: 99%
“…Attachment theory provides a framework useful for understanding the connection between relationships and dysphoria, as well as a theoretical basis for why an approach including partners could have incremental value in the treatment of perinatal depression (Marchand-Reilly and Reese-Weber 2005; Whiffen and Johnson 1998). Studies of attachment in adults have suggested romantic partners derive comfort and security from one another, want to be with their partner (particularly in times of distress), and protest when the partner is unavailable (Crowell and Waters 1994; Hazan and Shaver 1987).…”
Section: Introductionmentioning
confidence: 99%